Fractures and dislocation of the base of the thumb metacarpal. (January 2015) - Liverneaux, P. A.; Ichihara, S.; Hendriks, S.; Facca, S.; Bodin, F.
Acute traumatic lesions of the base of the first metacarpal are frequent and their consequences can affect the opposition of the thumb. They usually occur after trauma in compression along the axis of the thumb in flexion. Restoring the anatomy and biomechanics of the trapeziometacarpal joint is essential when treating these injuries, hence why surgical treatment is usually indicated. We distinguish trapeziometacarpal dislocations, small-fragment and large-fragment Bennett's fractures, articular three-fragment Rolando and comminutive fractures and extra-articular fractures of the base of the first metacarpal. All carry the risk of narrowing of the first web. Recent studies have described poor results with conservative treatment. Surgical techniques are varied: percutaneous surgery, open surgery and arthroscopic surgery. The techniques of osteosynthesis are various: locking plates, and direct or indirect screw fixation or pinning. The prognosis depends on the quality of the restoration of the mobility of the trapeziometacarpal joint. Level of evidence: 4